Letter to Nan Tepper from Jane Tolmach - Jane Tolmach:::::: (1976)
This exchange of letters between Jane Tolmach and KNXT Channel 2 News in May 1976 concerns media coverage of her Assembly campaign. On May 24, producer Nan Tepper requested a photograph, biography, press kit, and position papers for pre-election and election night coverage. On May 28, Tolmach responded by sending background and campaign materials and expressing hope that more women would be elected to office. She emphasized her support for women's participation in politics and offered to further communicate her views through the station's programming.